Mutual fund net flows in China: A co-holding network perspective - Yue Ma; Jichang Zhao; Shan Lu (Frontiers in Physics, 2023)
As the largest part of the mutual fund, open-end funds play a critical role in the Chinese mutual fund market. In this work, we construct an undirected weighted fund network of Chinese open-end funds based on the asset co-holding and explore whether funds’ co-holdings influence their net flows. The network structure traits are introduced into a panel data model to examine the impact of the asset co-holding network on fund flow changes. It is revealed that when a fund has more connections with other funds, indicated by a higher degree in the co-holding network, it receives more net flows. However, when the average co-holding value of a fund increases, its outflows outnumber the inflows. Furthermore, heterogeneity analysis suggests that this effect particularly exists for low-performance funds. The implications of these findings for fund investor behavior and the fund market are also discussed.